Inorganic sulfide and its manufacturing method

JP7668463B2Active Publication Date: 2025-04-25NATIONAL INSTITUTE OF ADVANCED INDUSTRIAL SCIENCE & TECHNOLOGY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2021197206
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-12-03
Publication Date
2025-04-25
Estimated Expiration
2041-12-03

AI Technical Summary

Technical Problem

Existing lithium-ion secondary batteries face safety concerns due to the use of flammable organic electrolytes, and conventional solid electrolytes like Li6PS5Cl phase have limitations in ionic conductivity and material selection, hindering the development of high-capacity batteries.

Method used

The synthesis of a cubic Li6PS5Br phase with a specific Br-type crystal structure and controlled elemental distribution, produced through a planetary milling process, which enhances ionic conductivity and capacity.

Benefits of technology

The new solid electrolyte material improves the charge-discharge characteristics and capacity of lithium-ion secondary batteries, offering a safer and more efficient alternative to conventional solid electrolytes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000012_0000
    Figure 00000012_0000
  • Figure 00000012_0001
    Figure 00000012_0001
  • Figure 00000013_0000
    Figure 00000013_0000
Patent Text Reader

Abstract

To disclose a solid electrolyte that is different from conventional solid electrolytes that can be used to manufacture a high-capacity all-solid-state lithium ion secondary battery.SOLUTION: An inorganic sulfide contains Li, P, S and Br and has a cubic Li6PS5Br type crystal phase with a lattice constant a of 9.937 to 9.964Å.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to inorganic sulfides and methods for producing the same. [Background technology]

[0002] Lithium-ion secondary batteries have attracted attention as high-energy-density batteries due to their high energy density compared to other secondary batteries, and their applications are expanding not only to portable devices (small consumer use) but also to in-vehicle and stationary applications such as social infrastructure. One of the requirements for these large lithium-ion secondary batteries is to improve safety while maintaining performance. Conventional lithium-ion secondary batteries (hereinafter sometimes referred to as "non-aqueous lithium-ion secondary batteries") use organic electrolytes and contain large amounts of flammable low-boiling point solvents (dimethyl carbonate, diethyl carbonate, ethylmethyl carbonate, etc.) that fall under the category of Class 4 hazardous materials, Class 2 petroleum, as viscosity reducers, raising concerns about battery ignition and smoke emission. Although companies are making efforts to improve safety, if the components can be changed, that is, if the electrolyte can be changed to a less flammable solid electrolyte, a dramatic improvement in safety can be achieved through material composition, which would reduce the cost and materials required for safety considerations and would be extremely useful industrially. In other words, one of the fundamental solutions to safety concerns is to replace organic electrolytes containing flammable solvents with flame-retardant solid electrolytes.

[0003] Solid electrolytes include polymer-based and inorganic types. However, polymer-based electrolytes currently exhibit low ionic conductivity below room temperature, and sufficient battery operation comparable to non-aqueous lithium-ion secondary batteries cannot be expected unless the temperature is above 60°C. On the other hand, as an inorganic type, sulfide solid electrolytes containing lithium sulfide (Li2S), phosphorus sulfide (P2S5), germanium sulfide (GeS2), etc., not only have high ionic conductivity approaching that of organic electrolytes even at room temperature, but also have lower grain boundary resistance compared to oxide solid electrolytes, making them one of the most promising solid electrolytes. β-Li3PS4 phase, Li 10 GeP2S 12 Known phases include Li6PS5Cl phase and Li7P2S8I phase.

[0004] Among these, the Li6PS5Cl phase is known as a particularly promising solid electrolyte material (see, for example, Non-Patent Document 1), and expectations for its application to batteries are high because it is compatible with carbon materials, which are typical negative electrodes used in lithium-ion secondary batteries. This material has conventionally been produced by solid-phase reaction methods, but recently, the inventors have found that by combining a vibratory mill and a planetary ball mill, materials with different constituent crystalline phases can be produced by mechanical milling alone, and that these materials not only have high ionic conductivity but also excellent plasticity (low Young's modulus) (see Patent Document 1). However, the required characteristics for battery performance are limitless, and in order to broaden the range of material selection, there is a need for a different solid electrolyte that can manufacture high-capacity lithium-ion secondary batteries. [Prior art documents] [Patent Documents]

[0005] [Patent Document 1] International Publication No. 2018 / 096957 [Non-patent literature]

[0006] [Non-Patent Document 1] S. Wang et al., J. Mater. Chem.,7,18612-18618 (2019). [Overview of the Initiative] [Problems that the invention aims to solve]

[0007] This invention has been made in view of the current state of the prior art described above, and its main objective is to provide a solid electrolyte different from conventional ones that can be used to manufacture high-capacity lithium-ion secondary batteries. [Means for solving the problem]

[0008] The inventors have diligently conducted research to achieve the above-mentioned objectives. As a result, they have found that having a cubic Li6PS5Br type crystal phase (hereinafter sometimes abbreviated as "LPSBr phase") with a lattice constant a of 9.937 to 9.964 Å increases the charge-discharge characteristics of an all-solid-state lithium-ion secondary battery compared to an LPSBr phase obtained by a conventional solid-state reaction method. Furthermore, the inventors have found that an LPSBr phase containing a cubic Li6PS5Br type crystal phase with a lattice constant a of 9.937 to 9.964 Å can be synthesized more easily than before by, for example, using a planetary milling apparatus capable of high-acceleration operation (i.e., a planetary milling apparatus capable of changing the centrifugal acceleration and revolution-orbit ratio of the planetary mill) for sample synthesis. In addition, the inventors have found that the ion distribution in the cubic Li6PS5Br type crystal phase obtained by the milling method differs from that obtained by the calcination method. Based on these findings, the inventors conducted further research and completed the present invention. Specifically, the present invention encompasses the following configuration.

[0009] Item 1. Contains Li, P, S and Br, An inorganic sulfide having a cubic Li6PS5Br-type crystalline phase with a lattice constant a of 9.937 to 9.964 Å.

[0010] Section 2. The cubic Li6PS5Br type crystal phase has the following space group:

[0011]

number

[0012] Item 3. The inorganic sulfide according to item 1 or 2, wherein the bromine occupancy at the 4a position in the cubic Li6PS5Br type crystal phase is 61.0% or less.

[0013] Item 4. An inorganic sulfide according to any one of items 1 to 3, wherein the phosphorus occupancy at the 4b position in the cubic Li6PS5Br type crystal phase is 90.0% or more and less than 100%.

[0014] Item 5. The inorganic sulfide according to any one of Items 1 to 4, containing 70.0 to 100% by mass of the cubic Li6PS5Br-type crystal phase with the total amount of the inorganic sulfide being 100% by mass.

[0015] Item 6. The inorganic sulfide according to any one of Items 1 to 5, having an ionic conductivity of 0.75 to 4.00 mS / cm.

[0016] Item 7. A method for producing the inorganic sulfide according to any one of Items 1 to 6, comprising: a step of subjecting raw material powder containing Li2S, LiBr, and P2S5 to milling treatment and the milling treatment is performed with the rotation of the sample container being the rotation of the inner rotor and the rotation of the mill body being the rotation of the outer rotor, and the rotation directions of the inner rotor and the outer rotor being opposite.

[0017] Item 8. The production method according to Item 7, having an internal-external rotation ratio of -3 to 0.

[0018] Item 9. A solid electrolyte for an all-solid-state lithium-ion secondary battery, containing the inorganic sulfide according to any one of Items 1 to 6.

[0019] Item 10. A binder material for an electrolyte layer of an all-solid-state lithium-ion secondary battery, containing the inorganic sulfide according to any one of Items 1 to 6.

[0020] Item 11. A binder material for an electrode of an all-solid-state lithium-ion secondary battery, containing the inorganic sulfide according to any one of Items 1 to 6.

[0021] Item 12. An all-solid-state lithium-ion secondary battery, comprising at least one of an electrolyte layer containing the solid electrolyte for an all-solid-state lithium-ion secondary battery according to Item 9 or the binder material for an electrolyte layer of an all-solid-state lithium-ion secondary battery according to Item 10, and an electrode containing the binder material for an electrode of an all-solid-state lithium-ion secondary battery according to Item 11.

Advantages of the Invention

[0022] According to the present invention, it is possible to provide a solid electrolyte different from conventional ones that can be used to manufacture high-capacity all-solid-state lithium-ion secondary batteries. [Brief explanation of the drawing]

[0023] [Figure 1] This shows the crystal structure of the cubic Li6PS5Br type crystalline phase of the inorganic sulfide of the present invention. The hatched areas show tetrahedra in which four anions are coordinated around a cation. [Figure 2] The X-ray diffraction patterns of the samples obtained in Example 1 are shown. The + marks represent the measured patterns, the solid lines represent the calculated patterns of the cubic Li6PS5Br type crystal phase, and the fitting residuals for these are also shown at the bottom. [Figure 3] This shows the charge-discharge characteristics evaluation results up to 30 cycles of NCA / In all-solid-state lithium-ion secondary batteries using the samples obtained in Example 1 and Comparative Example 1 as solid electrolyte materials. The upward-sloping curve represents the charging curve (subscript c), and the downward-sloping curve represents the discharging curve (subscript d). The numbers correspond to the number of cycles. [Figure 4] The X-ray diffraction patterns of the sample obtained in Comparative Example 1 are shown. The + indicates the measured pattern, and the solid line is the calculated pattern for the cubic Li6PS5Br type crystal phase. The fitting residuals for these patterns are also shown at the bottom. [Modes for carrying out the invention]

[0024] In this specification, "contains" is a concept that encompasses all of the following: "contains," "consist essentially of," and "consist of."

[0025] Furthermore, in this specification, the numerical range notation "A~B" means "greater than or equal to A and less than or equal to B".

[0026] Furthermore, in this specification, the term "all-solid-state lithium-ion secondary battery" is a concept that also includes all-solid-state lithium secondary batteries in which lithium metal is used as the negative electrode active material.

[0027] 1.Inorganic sulfides The inorganic sulfide of the present invention contains Li, P, S, and Br, and has a cubic Li6PS5Br type crystalline phase with a lattice constant a of 9.937 to 9.964 Å.

[0028] The inorganic sulfides of the present invention, in terms of ionic conductivity, lithium-ion secondary battery capacity, charge-discharge cycle characteristics, etc., specifically have the following properties: General formula (1): Li x P y S z Br (1) [In the formula, x, y, and z represent the following: 5.0 ≤ x ≤ 7.0, 0.7 ≤ y ≤ 1.3, and 3.0 ≤ z ≤ 7.0.] It is preferable to have a composition represented by .

[0029] In the inorganic sulfide of the present invention, in general formula (1), x, which is the Li content (corresponding to the amount of Li2S and LiBr used as raw materials when manufactured by the manufacturing method of the present invention described later), is preferably 5.0 to 7.0. This can be summarized as follows: Since ionic conductivity is proportional to the product of charge carrier concentration and mobility, increasing the Li content makes it easier to increase the charge carrier (Li ion) concentration and improve ionic conductivity, while also making it easier to improve capacity and charge-discharge cycle characteristics. Furthermore, in order to suppress the retention of Li2S as an impurity in the inorganic sulfide (the presence of a crystalline phase consisting of Li2S) which can become a source of hydrogen sulfide (H2S), x is preferably 5.0 to 7.0, more preferably 5.5 to 6.5, and even more preferably 5.7 to 6.3.

[0030] Furthermore, in the inorganic sulfide of the present invention, the P content y in general formula (1) (corresponding to the amount of P2S5 used as a raw material when manufactured by the manufacturing method of the present invention described later) is preferably 0.7 to 1.3, more preferably 0.8 to 1.2, and even more preferably 0.9 to 1.1. By setting y within the above range, Li2S is less likely to remain as an impurity in the inorganic sulfide (a crystalline phase consisting of Li2S is less likely to exist), making it easier to suppress the generation of hydrogen sulfide (H2S), and P2S5 is less likely to remain as an impurity (a crystalline phase consisting of P2S5 is less likely to exist), making it easier to suppress the decrease in ionic conductivity due to a decrease in lithium ion concentration.

[0031] Furthermore, in the inorganic sulfide of the present invention, the S content z in general formula (1) is preferably 3.0 to 7.0, more preferably 3.5 to 6.5, and even more preferably 4.0 to 6.0. By setting z within the above range, it becomes less likely that impurities other than the target substance (such as elemental sulfur) will be generated.

[0032] Figure 1 shows the crystal structure of the cubic Li6PS5Br type crystal phase of the inorganic sulfide of the present invention.

[0033] This crystal structure belongs to the cubic crystal system, and its space group is:

[0034]

number

[0035] In this structure, it is preferable that all cations are 4-coordinate bonds with anions. Furthermore, Br ions are present at positions 4a and 4c together with S ions and can bond with Li, which acts as a charge carrier at position 48h. Additionally, P at position 4b can bond with the adjacent S at position 16e to form PS4. 3- It can exist as an ion.

[0036] In this specification, "Type A crystalline phase" means that the composition may deviate slightly from A (for example, by about 0.1-10%, especially by about 0.2-5%), but the same crystalline structure is maintained.

[0037] The cubic Li6PS5Br type crystalline phase of the inorganic sulfide of the present invention has a lattice constant a of 9.937 to 9.964 Å (0.9937 nm to 0.9964 nm), preferably 9.940 to 9.955 Å (0.9940 to 0.9955 nm), and more preferably 9.945 to 9.950 Å (0.9945 to 0.9950 nm). When the lattice constant a is less than 9.937 Å (0.9937 nm), the ionic conductivity decreases, and the capacity of the lithium-ion secondary battery also decreases. Furthermore, when the lattice constant a is greater than 9.964 Å (0.9964 nm), the ionic conductivity also decreases, and the capacity of the lithium-ion secondary battery also decreases.

[0038] The cubic Li6PS5Br type crystalline phase of the inorganic sulfide of the present invention is preferably such that the bromine occupancy at position 4a is 61.0% or less, more preferably 30.0 to 57.5%, and even more preferably 45.0 to 55.0%, from the viewpoint of easily improving ionic conductivity and the capacity and charge / discharge cycle characteristics of lithium-ion secondary batteries. Similarly, the bromine occupancy at position 4c is preferably greater than 39%, more preferably 42.5 to 70.0%, and even more preferably 45.0 to 55.0%.

[0039] The cubic Li6PS5Br type crystalline phase of the inorganic sulfide of the present invention is preferably such that the phosphorus occupancy at the 4b position is 90.0% or more and less than 100%, more preferably 90.0 to 97.5%, and even more preferably 90.0 to 95.0%, from the viewpoint of easily improving ionic conductivity and easily improving the capacity and charge / discharge cycle characteristics of lithium-ion secondary batteries.

[0040] The inorganic sulfides of the present invention contain a cubic Li6PS5Br type crystalline phase, but when produced by the manufacturing method of the present invention described later, they do not contain an amorphous glass phase. In contrast, the inorganic sulfides produced by the method of Patent Document 1 or by solid-phase reactions often contain an amorphous phase in addition to the LPSBr phase, and the lattice constant a of the LPSBr phase is smaller than 9.937 or larger than 9.964 Å. In this case, the ionic conductivity is insufficient, and the capacity of the lithium-ion secondary battery is inferior.

[0041] The crystalline phase of the inorganic sulfide of the present invention is not particularly limited, but it is preferable that it does not contain Li2S-type crystalline phase, LiBr-type crystalline phase, P2S5-type crystalline phase, etc., which are raw material powders in the manufacturing method described later. In particular, by not including the Li2S-type crystalline phase, it is easier to suppress the generation of hydrogen sulfide, and thus an inorganic sulfide that is easy to handle even in low humidity environments can be obtained.

[0042] In the inorganic sulfides of the present invention, the abundance of the crystalline phase and elements (sometimes referred to as "elemental occupancy") is quantitatively analyzed by the Rietveld method of X-ray diffraction pattern analysis. The abundance of the crystalline phase and elements can be varied, for example, by the composition of the raw material powder, the milling conditions in the manufacturing method described later, and the heat treatment conditions after milling.

[0043] In the inorganic sulfide of the present invention, with the total amount of the crystalline phase being 100% by mass, the content of the cubic Li6PS5Br type crystalline phase (more specifically, the ratio of the cubic Li6PS5Br type crystalline phase estimated from the ratio of the peak intensity determined to originate from the cubic Li6PS5Br type crystalline phase and the peak of the glass phase among the X-ray diffraction peaks clearly observed when X-ray diffraction measurements are performed) is preferably 80.0 to 100% by mass or more, more preferably 85.0 to 100% by mass, and even more preferably 90.0 to 100% by mass.

[0044] The inorganic sulfide of the present invention, by having such a cubic Li6PS5Br type crystalline phase, can achieve high ionic conductivity (particularly lithium ion conductivity). Specifically, the ionic conductivity of the inorganic sulfide of the present invention can be set to 0.75 to 4.00 mS / cm, and particularly to 1.00 to 3.00 mS / cm. The ionic conductivity is measured by AC impedance after the obtained powder is formed into tablets. Note that if the inorganic sulfide of the present invention contains the glass phase and impurity phase described later, the ionic conductivity may decrease by the proportion of these components, and in some cases, the ionic conductivity of the inorganic sulfide of the present invention may be lower than the above lower limit.

[0045] On the other hand, the inorganic sulfide of the present invention may contain not only the cubic Li6PS5Br type crystalline phase described above, but also a glass phase. Furthermore, the inorganic sulfide of the present invention may also consist only of the crystalline phase described above, without the presence of a glass phase. However, in the present invention, a low proportion of the glass phase is preferable in order to improve ionic conductivity and capacity with the cubic Li6PS5Br type crystalline phase.

[0046] In the inorganic sulfide of the present invention, even if a glass phase is present, the relative abundance of the crystalline phase and the glass phase is quantitatively analyzed by peak profile fitting of both phases in the X-ray diffraction pattern. The relative abundance of the crystalline phase and the glass phase can be changed, for example, by the milling conditions in the manufacturing method described later, the heat treatment conditions after milling, etc. In the inorganic sulfide of the present invention, if a glass phase is present, the relative abundance of the crystalline phase and the glass phase is preferably 70:30 to 100:0 (mass ratio), and more preferably 80:20 to 100:0 (mass ratio), from the viewpoint of balancing the formability mainly provided by the glass phase and the ionic conductivity mainly provided by the crystalline phase. Furthermore, the chemical composition of the glass phase does not have to be the same as that of the crystalline phase.

[0047] In other words, in the inorganic sulfide of the present invention, the content of the cubic Li6PS5Br type crystalline phase is preferably 70.0 to 100% by mass, and more preferably 80.0 to 100% by mass, based on 100% by mass of the total amount of the inorganic sulfide of the present invention.

[0048] Furthermore, in the inorganic sulfide of the present invention, if an amorphous glass phase is included, the content of the amorphous glass phase is preferably 0 to 30.0% by mass, and more preferably 0 to 20.0% by mass, based on 100% by mass of the total amount of the inorganic sulfide of the present invention.

[0049] The inorganic sulfide of the present invention may contain the above-mentioned cubic Li6PS5Br type crystal phase, and may also contain a glass phase, but may also contain other impurity phases within a range that does not significantly affect the charge-discharge characteristics. Examples of such impurity phases include elemental sulfur (S), phosphorus sulfide (P2S5), lithium bromide (LiBr), and lithium sulfide (Li2S). However, in the present invention, in order to improve ionic conductivity and capacity with a specific cubic Li6PS5Br type crystal phase, it is preferable that the proportion of the impurity phase be low, and most preferably that there is no impurity phase at all. From this viewpoint, when the inorganic sulfide of the present invention contains an impurity phase, the impurity phase is usually preferably 0.1 to 10% by mass, and more preferably 0.2 to 5% by mass, with the total amount of the inorganic sulfide of the present invention being 100% by mass. The amount of the impurity phase is quantified by X-ray Rietveld analysis.

[0050] The shape of the inorganic sulfide of the present invention that satisfies the above conditions is not particularly limited, and any shape such as powder, granules, pellets, or fibers can be used. Furthermore, powdered inorganic sulfide is easily produced by the manufacturing method described later.

[0051] The inorganic sulfide of the present invention, satisfying the above conditions, has high ionic conductivity and can be used to manufacture high-capacity all-solid-state lithium-ion secondary batteries. For this reason, it is useful as a solid electrolyte constituting the electrolyte layer for all-solid-state lithium-ion secondary batteries, and also as a binder material for the solid electrolyte constituting the electrolyte layer for all-solid-state lithium-ion secondary batteries. Furthermore, it is also useful as a binder material for the positive and negative electrodes of all-solid-state lithium-ion secondary batteries.

[0052] 2. Method for producing inorganic sulfides The inorganic sulfide of the present invention can be obtained by a manufacturing method that includes, for example, a step of milling a raw material powder containing Li2S, LiBr, and P2S5, and the milling process is carried out using a planetary milling apparatus capable of changing the centrifugal acceleration and revolution-orbit ratio of the planetary mill. In other words, the inorganic sulfide of the present invention can be obtained by milling the above raw material powder using a planetary milling apparatus capable of high-acceleration operation.

[0053] In Patent Document 1, a two-stage milling process was performed using a high-speed milling apparatus and a low-speed milling apparatus in combination. However, in the present invention, by using the planetary milling apparatus described above, it is possible to produce the inorganic sulfide of the present invention in a single-stage milling process. In other words, it is useful in terms of simplifying the process and increasing the yield. Furthermore, as described above, the inorganic sulfide of the present invention has a cubic Li6PS5Br type crystalline phase, resulting in high ionic conductivity, which enables the manufacture of high-capacity lithium-ion secondary batteries.

[0054] The raw material powder can be appropriately selected depending on the composition of the inorganic sulfide to be ultimately obtained. In this invention, since the goal is to obtain a Li6PS5Br composition, it is preferable to use Li2S, LiBr, and P2S5.

[0055] In the planetary milling apparatus used in the manufacturing method of the present invention, the centrifugal acceleration and revolution-orbit ratio of the planetary mill can be changed, and the milling rotation speed can be independently controlled, with the rotation of the mill pot (sample container) being the rotational axis and the rotation of the mill body being the revolutional axis.

[0056] By controlling the rotational speeds of both the Earth and the Earth, the centrifugal acceleration of a planetary Mirr system can be calculated. Furthermore, the rotational-orbital ratio, which is the ratio of the rotational speeds of the Earth and the Earth, is defined as the rotational speed ratio R (rotational speed / orbital speed) plus 1 (R+1).

[0057] In addition, the centrifugal acceleration of the planetary mill and the revolution angular velocity ω1 have the following relational expression: Centrifugal acceleration of planetary mill (m / s 2 ) = ω1 2 (G + D(1 + R) 2 ) / 2g [In the formula, ω1 represents the revolution angular velocity (1 / s). G represents the revolution diameter (m). D represents the inner diameter of the mill pot (m). R represents the rotation speed ratio. g represents the gravitational acceleration.] holds true.

[0058] The revolution angular velocity (1 / s) is defined as the revolution rotation speed (rpm) ÷ 60 (s) × 2π (= rotation speed × 0.1047). The rotation speed is the measured value at an inverter frequency of 60 Hz. From the perspective of easily forming the cubic crystal Li6PS5Br type crystal phase and easily obtaining the inorganic sulfide of the present invention, the rotation speed is preferably 100 to 500 rpm and more preferably 200 to 400 rpm during revolution. Also, from the perspective of easily forming the cubic crystal Li6PS5Br type crystal phase and easily obtaining the inorganic sulfide of the present invention, the rotation speed is preferably 500 to 1000 rpm and more preferably 700 to 900 rpm during rotation.

[0059] In addition, the directions of rotation and revolution are defined as + for clockwise and - for counterclockwise. That is, when the rotation directions of rotation and revolution are the same, the rotation-revolution ratio is a positive value, and when the rotation directions of rotation and revolution are different and the rotation speed ratio is 1 or more, the rotation-revolution ratio is a negative value. The rotation-revolution ratio becomes zero only when the rotation speed ratio is 1 and the rotation directions are opposite. In the present invention, from the perspective of easily forming the cubic crystal Li6PS5Br type crystal phase, having a high ionic conductivity of the obtained inorganic sulfide, and easily increasing the capacity and charge-discharge cycle characteristics when manufacturing a lithium-ion secondary battery, the rotation directions of rotation and revolution are opposite, that is, the rotation-revolution ratio is preferably a negative value. Specifically, -3 to 0 is preferable, and -2.5 to -0.5 is more preferable. From the above, the manufacturing method of the present invention can also be described as a method of performing a milling process in which the rotation of the sample container is rotation, the rotation of the mill body is revolution, and the rotation directions of rotation and revolution are opposite.

[0060] In this invention, using a milling apparatus based on the above principle, the planetary mill centrifugal acceleration is set to 20-60 G (unit G = 9.80665 m / s²) from the viewpoint of suppressing impurities such as Li2S. 2 ) is preferred, and 30-50G is more preferred.

[0061] Furthermore, the milling time is not particularly limited, but is preferably 10 to 100 hours, and more preferably 20 to 80 hours. The milling temperature is also not particularly limited and can be 0 to 70°C (for example, room temperature).

[0062] The specific manufacturing method involves first filling the container of a milling apparatus based on the above principle with raw material powder in an ultra-low humidity environment (dew point below -60°C) (such as a glove box, dry room, or open dry chamber). There are no particular restrictions on the type of container that can be used, but lining the inner wall of a metal container with ceramic materials such as agate, alumina, or zirconia can help prevent contamination from the metal material. The amount of raw material to be filled is not particularly limited and depends on the pot volume, but for example, in the case of a 500cc container, it can be about 10 to 100g, preferably about 30 to 80g. One example of a preferred filling configuration is to fill about 1 / 3 of the pot's internal volume with raw material and about 1 / 3 with grinding media such as beads. It is preferable to add grinding media (zirconia beads, etc.) to the raw material powder as needed, seal it, remove it, and set it in the milling apparatus. After milling, the product may adhere strongly to the container. If necessary, the container can be returned to an extremely low humidity environment (dew point below -60°C) (e.g., a glove box), the product can be scraped off the container walls, and then the same process can be repeated. After processing, the product can be removed in an extremely low humidity environment (dew point below -60°C) (e.g., a glove box), sealed in a sealed container, and then various evaluations such as X-ray diffraction measurement, ionic conductivity measurement, and charge / discharge characteristic evaluation can be performed.

[0063] In this manner, the inorganic sulfide of the present invention is obtained, but it can also be subjected to heat treatment as needed. This can further improve crystallinity or increase the amount of crystalline phase to further enhance ionic conductivity, making it possible to adjust the ratio of crystalline phase to glass phase according to the required properties. In this case, the heating temperature is preferably kept as low as possible to take advantage of the characteristics of the milled sample, preferably 100 to 500°C, and more preferably 200 to 400°C. There are no particular restrictions on the heating time, but it is preferably 0.5 to 100 hours, and more preferably 1 to 50 hours.

[0064] 3. Lithium-ion rechargeable batteries The all-solid-state lithium-ion secondary battery using the inorganic sulfide of the present invention can be manufactured by known methods.

[0065] For example, when the inorganic sulfide of the present invention is used as a binder material for the positive electrode, a known lithium nickel cobalt manganese-based or lithium nickel cobalt aluminum-based composite oxide can be used as the positive electrode material, and the inorganic sulfide of the present invention can be used as the binder material to manufacture the positive electrode by a known method. In other words, the inorganic sulfide of the present invention can be used as a substitute material for commonly used binder materials such as PTFE and PVDF to manufacture the positive electrode. Furthermore, in all-solid-state lithium-ion secondary batteries, as is well known, a lithium ion conductor such as LiNbO3 or Li4Ti5O3 is placed on the surface of the oxide positive electrode active material. 12 A predetermined amount (e.g., 0.5 mol%) of oxide material may be coated onto the surface.

[0066] Furthermore, when the inorganic sulfide of the present invention is used as a binder material for the negative electrode, known materials such as metallic indium, metallic lithium, carbon-based materials (activated carbon, graphite, etc.), silicon, silicon oxide, Si-SiO-based materials, and lithium titanium oxide can be used as the negative electrode material, and the inorganic sulfide of the present invention can be used as the binder material to manufacture the negative electrode by known methods. In other words, the inorganic sulfide of the present invention can be used as a substitute material for commonly used binder materials such as PTFE and PVDF to manufacture the negative electrode.

[0067] Furthermore, when the inorganic sulfide of the present invention is used as a solid electrolyte in an electrolyte layer, the inorganic sulfide of the present invention can be formed into layers by conventional methods and used as an electrolyte layer. When the inorganic sulfide of the present invention is used as a binder material in an electrolyte layer, an electrolyte layer can be manufactured by known methods using various solid electrolytes as the solid electrolyte and the inorganic sulfide of the present invention as the binder material. In other words, an electrolyte layer can be manufactured by using the inorganic sulfide of the present invention as a substitute material for PTFE and other materials that are commonly used as binder materials.

[0068] Furthermore, all-solid-state lithium-ion secondary batteries can be assembled using other known battery components in accordance with conventional methods. [Examples]

[0069] The following examples and comparative examples will be shown to further clarify the features of the present invention, but the present invention is not limited to the following examples.

[0070] [Example 1 and Reference Example 1] Inside a glove box, 17 20mm diameter zirconia beads were placed in a 500cc zirconia-lined metal container. Then, raw material powder adjusted to a Li6PS5Br composition (Li2S:LiBr:P2S5 molar ratio = 5:2:1; Li2S is 14.6864g, LiBr is 11.1042g, and P2S5 is 14.2094g) was weighed and added to a pot. The total amount of raw material powder added was 40g. After sealing the pot, it was removed from the glove box and set in a planetary milling machine (Hygee BX382 manufactured by Kurimoto Iron Works Co., Ltd.) capable of changing the centrifugal acceleration and revolution-orbit ratio. The revolution speed was set to 357 rpm, the rotation speed to 842 rpm, and the rotation and revolution directions were reversed, resulting in a revolution-orbit ratio of -1.359. Milling was performed for 64 hours with a centrifugal acceleration of 40.1G. After milling, the sample containers were placed back into the glove box, opened, and the samples were collected. The yield was approximately 95%.

[0071] The X-ray diffraction pattern of the obtained sample is shown in Figure 2. Profile fitting of the X-ray diffraction pattern (2θ = 27~34°) was performed to quantify the glass phase. The amorphous glass phase, which is also observed in the Li6PS5Br composition obtained from Example 16 of Patent Document 1 (indicated as Reference Example 1), was not detected, and the space group was:

[0072]

number

[0073] The value of the lattice constant a, determined from the peak position of the X-ray diffraction pattern, was 9.9454 (8) Å (0.99454 (8) nm). Compared with the lattice constant a of the Li6PS5Br composition obtained from Example 16 of Patent Document 1 (reference example), which was 9.9365 (9) Å (0.99365 (9) nm), it is clear that the cubic Li6PS5Br type crystal phase of the inorganic sulfide of the present invention has a larger lattice constant a than the conventional cubic Li6PS5Br type crystal phase. It is also clear that it is smaller than the lattice constant value of the comparative example sample described later (9.96472 (17) Å (0.996472 (17) nm)).

[0074] The structural model was obtained from the Li6PS5Br structure in Figure 1. The isotropic thermal vibration factor values ​​of all cations and anions were fixed to 1, and the occupancy rates were determined. The lithium (Li) occupancy rate at position 48h was fixed to 0.5, and the phosphorus (P) occupancy rate at position 4b was also varied from an initial value of 1. A linear constraint condition was applied to the bromine (Br) occupancy rate such that the sum of the occupancy rates at positions 4a and 4c was 1. At positions 4a and 4c, a linear constraint condition was applied so that the sum of the occupancy rates of sulfur (S) and bromine (Br) was 1. A linear constraint condition was also applied at position 16e so that the sum of the occupancy rates of sulfur (S) and bromine (Br) was 1. The occupancy rates of each element at each lattice position obtained in this way are shown in Table 1. For comparison, a Li6PS5Br composition sample obtained from Example 16 of Patent Document 1 is also shown as Reference Example 1, applying the same structural model as Example 1 and Comparative Example 1. If the occupancy rate at each grid position exceeds 1, it becomes a meaningless value, so it was fixed at 1.

[0075] [Table 1]

[0076] Table 1 shows that the example sample has a bromine occupancy rate (g) at position 4a. 4a The Br) ratio was 0.533(4), which is clearly lower than the comparative example sample (0.690(3)) and the reference example sample (0.616(4)) described later. Furthermore, the phosphorus occupancy (g) at position 4b of the example sample was 0.533(4). 4b The value of P is 0.912(6), which is smaller than that of comparative example sample (1) described later, and larger than that of reference example sample (0.889(6)). From the above, it can be seen that the inorganic sulfide of the present invention has a novel crystal structure and elemental distribution that differs from conventional materials.

[0077] Furthermore, the ionic conductivity determined by the AC impedance method was 1.33 mS / cm, which is higher than the 0.48 mS / cm in Reference Example 1, indicating that it possessed sufficient properties as a solid electrolyte.

[0078] Next, 30.1 mg of the obtained sample and 0.5 mol% LiNbO3 coated lithium nickel cobalt aluminum oxide cathode active material (LiNi 0.8 Co 0.15 Al 0.05 70.1 mg of O2 (hereinafter sometimes referred to as "LiNbO3 coated NCA" or simply NCA) was mixed in a glove box to prepare a positive electrode composite material. 79.5 mg of the obtained sample was placed in a polyethylene terephthalate (PET) tube as the electrolyte layer, compressed at 144 MPa, then 10.1 mg of the above positive electrode composite material was added and compressed at 360 MPa. A 10 mm diameter In foil (0.05 mm thick) was attached to the opposite side of the positive electrode layer and compressed at 144 MPa to prepare a battery element. This element was placed in an all-solid-state battery, and pressure was applied from above and below the element to achieve a current density of 64 μA / cm². 2 The charge-discharge test was performed 30 times in a potential range of 2.1-3.7V, starting at room temperature. The results, along with those of Comparative Example 1, are shown in Figure 3.

[0079] As shown in Figure 3, the sample obtained in Example 1 had a larger charge / discharge capacity from the first charge to 30 cycles compared to the sample in Comparative Example 1 (the initial and 5-cycle discharge capacities of the Example 1 sample were approximately 164 and 139 mAh / g, respectively), indicating that it is suitable for use as an electrolyte material for lithium-ion secondary batteries. Furthermore, in the charge / discharge characteristics of the Reference Example 1 sample shown in Figure 20 of Example 16 in Patent Document 1, the initial and 5-cycle discharge capacities were approximately 112 and 91 mAh / g, respectively, which is inferior to the Example 1 sample. This shows that the Example 1 sample has superior charge / discharge characteristics compared to the Reference Example 1 sample.

[0080] [Comparative Example 1] In a glove box, 0.7348 g of Li2S, 0.5551 g of LiBr, and 0.7105 g of P2S5 (total 2 g; Li2S:LiBr:P2S5 molar ratio = 5:2:1) were weighed and placed in a zirconia container with zirconia balls, sealed, and removed from the glove box. The mixture was then ground in a planetary ball mill at 500 rpm for 20 hours. After grinding, a pot was reintroduced into the glove box, the powder was collected, and pressed at 128 MPa to produce 15 mmΦ pellets. These pellets were then placed in an electric furnace and heat-treated at 550°C in vacuum for 2 hours. The yield was approximately 73%. Figure 4 shows the fitting results of the X-ray diffraction patterns of the obtained samples. In Comparative Example 1, the glass phase was quantified using the same method as in Example 1, and no amorphous glass phase was detected.

[0081] The value of the lattice constant a obtained by Rietveld analysis is 9.96472(17) Å (0.996472(17) nm), which is clearly larger than that of the sample in Example 1. The cation and anion occupancy is shown in Table 1. From Table 1, it can be seen that the sample in Comparative Example 1 has a different lattice constant a and phosphorus occupancy (g) at position 4b compared to the sample in Example 1. 4b,P ) and bromine occupancy at position 4a (g 4a,Br It is clear that it has ).

[0082] Furthermore, from the charge-discharge characteristics of the lithium secondary battery using the Comparative Example 1 sample, which was prepared under the same conditions as Example 1 (Figure 3), it is clear that the lithium secondary battery using the Comparative Example 1 sample has a lower charge-discharge capacity up to 30 cycles compared to the lithium secondary battery using the Example 1 sample. The ionic conductivity value of Comparative Example 1, 2.51 mS / cm, is higher than that of Example 1, but its charge-discharge characteristics are inferior, indicating that simply having high ionic conductivity does not improve charge-discharge capacity.

[0083] From the above, it has become clear that the lithium secondary battery using the inorganic sulfide of the present invention, which contains a crystalline phase having a unique crystal structure and elemental distribution, has excellent charge and discharge characteristics. [Industrial applicability]

[0084] The inorganic sulfides of the present invention can be used, for example, as solid electrolytes for large all-solid-state lithium-ion secondary batteries for automotive and stationary use where safety is required, as well as binder materials for solid electrolytes and binder materials for solid battery electrodes.

Claims

1. Contains Li, P, S and Br, and Cubic Li with a lattice constant a of 9.937 to 9.964 Å 6 P.S. 5 An inorganic sulfide having a Br-type crystal phase.

2. The cubic Li 6 P.S. 5 The Br-type crystalline phase has the space group: [Equation 1] The inorganic sulfide according to claim 1, which is

3. The cubic Li 6 P.S. 5 3. The inorganic sulfide according to claim 1, wherein the bromine occupancy rate at the 4a position in the Br-type crystal phase is 61.0% or less.

4. The cubic Li 6 P.S. 5 The inorganic sulfide according to any one of claims 1 to 3, wherein the phosphorus occupancy rate at the 4b position in the Br-type crystal phase is 90.0% or more and less than 100%.

5. The total amount of the inorganic sulfides is 100 mass%, and the cubic Li 6 P.S. 5 The inorganic sulfide according to any one of claims 1 to 4, containing 70.0 to 100 mass% of a Br-type crystalline phase.

6. The inorganic sulfide according to any one of claims 1 to 5, having an ionic conductivity of 0.75 to 4.00 mS / cm.

7. The method for producing an inorganic sulfide according to any one of claims 1 to 6, Li 2 S, LiBr and P 2 S 5 A process of milling the raw material powder containing and wherein the milling process is performed such that the rotation of the sample container is rotation on its axis and the rotation of the mill body is revolution, and the rotation and revolution are performed in opposite directions.

8. The manufacturing method according to claim 7, wherein the rotation-revolution ratio is −3 to 0.

9. A solid electrolyte for an all-solid-state lithium ion secondary battery, comprising the inorganic sulfide according to any one of claims 1 to 6.

10. A binder material for an electrolyte layer of an all-solid-state lithium ion secondary battery, comprising the inorganic sulfide according to any one of claims 1 to 6.

11. A binder material for electrodes of an all-solid-state lithium ion secondary battery, comprising the inorganic sulfide according to any one of claims 1 to 6.

12. 12. An all-solid-state lithium-ion secondary battery comprising at least one of an electrolyte layer containing the solid electrolyte for an all-solid-state lithium-ion secondary battery according to claim 9 or the binder material for an electrolyte layer of an all-solid-state lithium-ion secondary battery according to claim 10, and an electrode containing the binder material for an electrode of an all-solid-state lithium-ion secondary battery according to claim 11.